Best Answer

That doesn't factor neatly. Using the quadratic formula, we find two real solutions:

(-1 plus or minus the square root of 37) divided by 6

x = 0.8471270883830365

x = -1.18046042171637

Study guides

☆☆

More answers

(x - 1)(x2 + x + 4)

It factors as

(x2 -2x+2)(x2 +2x+2)

The expression has no real factors.

x2(x + 3)

(x+2) (x-1)

(x-6) (X+2)

3(x+1)

Q: Factorize 3x2 plus x - 3 .?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

I could factorize : (3 + x) (17 + 3 x) But have no idea about the next part...

3x2-2x-21 = (3x+7)(x-3)

Step 1: 3(x2 + 7x - 44) Step 2: 3(x + 11)(x - 4)

6x(3x2 - x + 4)

3x2 - 9x - 912 = 3(x2 - 3x - 304) = 3(x - 19)(x + 16).

Related questions

3x2+x-2 = (3x-2)(x+1) when factored

If you meant 3x2 - 5x + 2, here is your answer 3x2 - 5x +2 = 0 => 3x2 - 3x - 2x + 2 = 0 => 3x(x-1) - 2(x-1) = 0 => (3x - 2) (x-1) = 0 => x = 2/3 or, x = 1

3x2 + 10x + 3 = (x + 3)(3x + 1).

x3 - 3x2 + x - 3 = (x - 3)(x2 + 1)

x3 - 3x2 + x - 3 = (x2 +1)( x - 3)

3x2 + 48 + 192 = 3x2 + 240 = 3 (x2+ 80)

I could factorize : (3 + x) (17 + 3 x) But have no idea about the next part...

It is (x-3)(x-4) when factored

3x2 + 2x + 3 + x2 + x + 1 = 4x 2+ 3x + 4

-3(x - 3)(x + 1)(x + 1)

3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)

3x2 + 2x - 21 = (3x - 7) (x + 3)